2007
DOI: 10.1093/jjco/hym085
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Drinking and Total Cancer Risk: An Evaluation Based on a Systematic Review of Epidemiologic Evidence among the Japanese Population

Abstract: We conclude that there is convincing evidence that alcohol drinking increases the risk of total cancer in the Japanese population, specifically among heavy drinking men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A significant difference in risk on females compared to males is also noted. Other authors (Inoue et al, 2007) found no relationship between alcohol consumption and increased risk for the development of cancer in women. These studies also report that the risk becomes greater in individuals who consume alcohol and tobacco simultaneously (Inoue et al, 2007;Bagnardi et al, 2011).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A significant difference in risk on females compared to males is also noted. Other authors (Inoue et al, 2007) found no relationship between alcohol consumption and increased risk for the development of cancer in women. These studies also report that the risk becomes greater in individuals who consume alcohol and tobacco simultaneously (Inoue et al, 2007;Bagnardi et al, 2011).…”
Section: Discussionmentioning
confidence: 87%
“…Other authors (Inoue et al, 2007) found no relationship between alcohol consumption and increased risk for the development of cancer in women. These studies also report that the risk becomes greater in individuals who consume alcohol and tobacco simultaneously (Inoue et al, 2007;Bagnardi et al, 2011). However, even though alcohol and tobacco are factors that act synergistically, ensuring the increased risk, alcohol is considered an independent risk factor for many types of cancer (Pelucchi et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…This project was conducted in parallel with systematic reviews of the relevant literature 11. Topics for the pooled analysis were determined from discussions of the scientific evidence and public health implications 12 13.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the association between alcohol intake and cancer, even when moderate, alcohol intake is shown to be associated with an increased risk of cancer in studies conducted in Japan and abroad . In the IARC report, alcohol intake was identified as a factor promoting carcinogenesis in the oral cavity, the pharynx, the esophagus, the colon, the liver, and the breast .…”
Section: Mechanisms Through Which the Risk Of Cancer Is Assumed To Bementioning
confidence: 99%